First person - Emily Koller (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Emily Koller is first author on ' Temporal and spatially controlled APP transgene expression using Cre-dependent alleles', published in DMM. Emily is a postdoctoral associate in the lab of Joanna Jankowsky, PhD at Baylor College of Medicine, Houston, TX, USA, investigating the impact of ageing in Alzheimer's disease, and is also interested in developing therapeutic interventions for diseases of the brain.